(3GfKdGL GdQeVGA ef GdUOhQ aj GNJdGL GdCYVGAs - (3eMeO GdSeGhj , eMeO Hf WGgQ GdSeGhj,J (B1370 (3g` s
(3ChdgG (B:s
(3MeOkG def YQa CQHGH GdaWf YbHi GdCehQ HGNJdGLGJ GdHOf s
(3BNQgG (B:s
(3Hdi hLOJ eG Qhi GdeYdi aRhOJg HfXei GdeYdi aGdMeO ddg Ydi GdJeGe hCaVd GdUdGI hGdSdGe Ydi eMeO fHi GdQMeI hBdg GdCcGHQ GdCFeI Je s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B173s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdaQGSIs